2007
DOI: 10.1159/000101784
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Causes of Bronchiectasis: Primary Immune Deficiencies and the Lung

Abstract: Primary immune deficiencies (PID) comprise a heterogeneous group of genetically determined disorders that affect development and/or function of innate or adaptive immunity. Consequently, patients with PID suffer from recurrent and/or severe infections that frequently involve the lung. While the nature of the immune defect often dictates the type of pathogens that may cause lung infection, there is substantial overlap of radiological findings, so that appropriate laboratory tests are mandatory to define the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 168 publications
0
34
0
2
Order By: Relevance
“…Bronchiectasis is still an important health care problem in developing countries 1,3,4 . In children with BE usually slowly persisting chronic respiratory symptoms are present 14,15. In cases with chronic productive cough and relapsing lower airway infections clinician should be suspicious for BE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchiectasis is still an important health care problem in developing countries 1,3,4 . In children with BE usually slowly persisting chronic respiratory symptoms are present 14,15. In cases with chronic productive cough and relapsing lower airway infections clinician should be suspicious for BE.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is not clearly understood 1,2 . Advances in sanitation, development in nutritional status, use of effective antibiotics for respiratory tract infections, success in childhood immunization (especially measles and pertussis) have led to a decrease in the disease 1,3,4 . In developed countries BE secondary to cystic fibrosis (CF) is common, but in less developed countries non-CF bronchiectasis is more frequent.…”
mentioning
confidence: 99%
“…Patients with PADs are at a significantly increased risk for developing bronchiectasis [65,68,69], as we indicated in a study in which 37.5% of patients with bronchiectasis were diagnosed with defects in antibody-mediated immunity [70]. The exact prevalence of bronchiectasis in patients with PAD is unclear, although a systematic review has reported that bronchiectasis manifests in 17%-76% of cases, usually with a tubular/ cylindrical pattern affecting the proximal bronchi [71].…”
Section: Bronchiectasismentioning
confidence: 97%
“…In the absence of a specific etiology, patients undergo a wide range of diagnostic procedures to identify hereditary and non-hereditary diseases [18]. The major genetic causes of non-CF bronchiectasis are primary immune deficiencies and primary ciliary dyskinesia (PCD) [19, 20]. Acquired causes of non-CF bronchiectasis are chronic aspiration, foreign body inhalation and extrinsic airway compression [3, 18].…”
Section: Introductionmentioning
confidence: 99%